MHC class I molecules are an essential cell surface component involved in Theileria parva sporozoite binding to bovine lymphocytes - Shaw, M.K.; Tilney, L.G.; Musoke, A.J.; Teale, A.J. (1995)
The major histocompatibility complex (MHC) class I molecules are ubiquious cell surface molecules involved in the cell-mediated immune response. We show here, using a number of different, independent approaches, that these proteins are an essential component of the host cell surface receptor involved in Theileria parva sporozoite invasion. Monoclonal antibodies (mAbs) reactive with common determinants on MHC class I molecules and with B-2 microglobulin inhibites sporozoite entry by specifically preventing the intitial binding event. However, in experiments using lymphocytes from heterozygous cattle in which at least four MHC class I gene products are expressed, mAbs which reacted with only one of these products did not inhibit entry. Using a series of bovine deletion mutant cell lines from which one or both MHC class I haplotypes had been lost, sporozoite binding and entry clearly correlated with the level of class I surface expression. While the elevel of sporozoite entry into cells in which one of the MHC class I haplotypes was lost was only slightly lower than into the parent cells, in a double deletion cell line having less than 5 percent of the class I expression of the parent cells the level of infection was only 4.3% of that into the parent cells. Furthermore, sporozoite entry into cells from a spontaneously arising mutant cell line exhibiting low levels of class I expression was correspondingly low. Treatment of lymphocytes with IL-2 produced a significant increase in host cell susceptibility and sporozoite entry and this increase correlated with either an increase in the number of target molecules per host cell, or in the binding of bovine MHC class I molecules to the mAbs. In particular, a significant increase in the level of reactivity with mAb W6/32 was observed. Lastly, we show that parasite entry can be competitively inhibited with an isolated sporozoite surface protein, p67. However, p67 binds weakly to lymphocyte surface molecules and initial attemps to use p67 to isolate the relevant host cell molecule(s) have not been successful.